An extremal problem on the potentially wheel graph sequences - Chen, Gang; Zhang, Qiang (Utilitas Mathematica, 2017)
Gould, Jacobson and Lehel considered a variation of the classical Turán-type extremal problems: for a given graph H1 determine the smallest even integer σ(H, n) such that every n-term graphic sequence π = (d1,d2,⋯, dn) with σ(π) = d1 + d2 + ⋯ + dn ≥ σ(H, n) has a realization G containing H as a, subgraph. In this paper, we determine the values of σ(Wr,n) for r ≥ 6 and n sufficiently large, where Wr is the wheel graph on r vertices.